Impact of pharmaceutical validation on prescribing errors in a neonatal intensive care unit. Randomised and controlled study - Canales-Siguero, M. D.; García-Muñoz, C.; Caro-Teller, J. M.; Piris-Borregas, S.; Martín-Aragón, S.; Ferrari-Piquero, J. M.; Moral-Pumarega, M. T.; Pallás-Alonso, C. R. (Frontiers in Pediatrics, 2024)
To compare the frequency of electronic prescription errors when the prescription was validated by the clinical pharmacist versus when it was not.This prospective randomised controlled study was conducted in three phases. A randomised phase, in which patients were divided into control and intervention groups, and a pre-and postintervention phase were consecutively performed to analyse the impact of pharmaceutical validation of prescriptions in a neonatal intensive care unit (NICU). This study was performed at a highly complex NICU at a tertiary hospital.All patients born during the study period who were admitted to the NICU, with a stay lasting ≥24 h, and received active pharmacological treatment were included in the study.Pharmaceutical validation was performed according to the paediatric pharmaceutical care model. A high level of validation was selected for this study. In the intervention group, discrepancies found during the review process were communicated to the medical team responsible for the patients and resolved on the same day.In total, 240 patients were included in this study. Sixty-two patients were allocated to the preintervention (n=38) or post-intervention (n = 24) groups, and 178 patients were randomly sorted into two groups, control (n=82 newborns) and intervention (n=96 newborns). During the randomisation phase, the number of prescription errors detected was significantly lower in the intervention group than that in the control group (129 vs. 270; p<0.001). Similarly, prescription errors reaching the patient were significantly reduced from 40% (n=108) in the control group to 1.6% (n=2) in the intervention group. In the pre-and post-intervention periods, the prescription lines containing prescription errors decreased from 3.4% to 1.5% (p=0.005).This study showed that the pharmaceutical validation process decreased both the number of errors in the electronic prescribing tools and the number of prescription errors reaching the patient.